Preparation of Bio-Oil and Biochar through Co-Pyrolysis of Pennisetum purpureum and HDPE Plastic Waste at Various Feedstock Ratios and Temperatures - Asfihani Asfihani; Azhari Azhari; Adi Setiawan (Reaktor, 2026)
This study investigates the co-pyrolysis process of elephant grass (Pennisetum purpureum) and HDPE plastic waste and evaluates the properties of the resulting bio-oil and biochar. The process was conducted in a pilot-scale reactor under a nitrogen atmosphere using a two-stage heating scheme at 300°C and 450°C, with biomass–HDPE weight ratios of 100:0, 90:10, 75:25, 60:40, and 50:50. The method used in this work includes product yield analysis, thermophysical characterization, GC–MS-based chemical composition analysis, and ANOVA statistical validation to determine the optimum conditions for Pennisetum purpureum–HDPE co-pyrolysis process. The results indicate that the addition of HDPE does not increase the absolute yield of bio-oil but significantly enhances its energy quality. The calorific value of the bio-oil increased from 10,579 cal/g for pure biomass to a maximum of 12,029 cal/g at a 75:25 biomass–HDPE weight ratio, accompanied by a compositional shift from oxygenated compounds toward the dominance of fatty acid methyl esters (FAME) and medium- to long-chain hydrocarbons. At the same ratio, biochar achieved the highest yield (44.93% w/w) while maintaining characteristics suitable for energy applications. These findings identify the 75:25 biomass–HDPE ratio as the optimum condition based on both experimental and statistical evidence, and demonstrate that biomass–HDPE co-pyrolysis is an effective strategy for waste utilization and for enhancing the quality of renewable energy products.